Closure of special atomic subsets of semantic model - Yeshkeyev, A.R.; Issaeva, A.K.; Popova, N.V. (KSU publ., 2020)
The present paper concerns some properties of the so-called small models, generally speaking, not necessarily complete theories and their relationship with each other. In the well-known paper [1], R. Vaught have proved the fundamental theorem-criterion on the behavior of countable prime and atomic models for complete theories in countable language. The essence of this criterionis that in a complete theory any countable prime model is at the same time an atomic model of this theory. The result obtained in this paper is related to the classical problem of Vaught about countably prime models of complete theories but in more general formulation of the notion of countable atomicity. The main result of this paper is that it focuses on the syntactic properties on special subsets of a fragment of the semantic model the specific Jonsson theory. The concept of the so-called model-theoretic ¾rheostat¿ was also used to obtain results related to the refinement of the concept of atomicity in the framework of Jonsson’s theories.
Keywords: Jonsson theory; semantic model; existentially prime model; atomic model; core model